Effect of fire on behavior of RC beam-column assembly under a middle column removal scenario. (15th May 2023) - Jin, Liu; Lan, Dongqiu; Zhang, Renbo; Qian, Kai
Abstract: Fire is one of the accidental loads that can result in the progressive collapse of buildings. To investigate the structural behavior of reinforced concrete (RC) structures subjected to fire-induced progressive collapse, the sequential thermal-mechanical coupling (STMC) method is adopted. The STMC method includes two steps: firstly, the fire effects (temperature field) on the material properties of concrete and reinforcement are simulated. Secondly, the results of the first step are set as the initial condition of the RC beam-column assembly to study the structural behavior of the assembly subjected to a middle column removal scenario. The reliability of the simulation method is validated against the available test results. The influences of fire duration and fire range are studied based on the validated numerical model. It is found that the load resistance and deformation capacity decrease significantly as the fire duration exceeds 30 min. The load resistances of the RC beam-column assemblies under the fire durations of 30 min, 60 min, and 90 min are 35%, 26%, and 21% of that of the RC beam-column assembly under the ambient temperature, respectively. Fire duration of 18 min is found to be the critical one, less than and greater than which the failure of the RC beam-column assembly is controlled by the fracture of the beam bottom rebar near the middle column and the fracture of the beam top rebar at the location of rebar termination, respectively. The RC beam-column assembly subjected to a single-bay in fire scenario shows asymmetric structural behavior. Compared with RC beam-column assemblies under two-bay in fire scenario, the load resistances of RC beam-column assemblies subjected to single-bay in fire scenario are greater by 6%–30%. However, they achieve a similar deformation capacity as the failure of the RC beam-column assemblies subjected to single-bay in fire scenario is controlled by the failure of the bay in fire. Highlights: The sequential thermal-mechanical coupling method is introduced to simulate the fire effect on the material property. The load transfer paths of fire-exposed RC frames under a middle column removal scenario are revealed. The effects of fire duration and fire range on the load resisting mechanism and failure mode of RC frame are quantified.